P1_8 Ice Ice, Maybe - Michelbach, Christian; Holmes, Luke; Treacher, Dan (Physics Special Topics, 2014)
Many types of water ice can have semiconducting properties, particularly when doped, due to their crystalline structure. These properties may possibly lend the material to being used to create photovoltaic cells on distant planetary bodies. A band gap of 7.8 eV for cubic ice and 5.15 eV for ice XI give a solar spectral radiance of 1.51x10-11 W sr-1 m-2 Hz-1 and 9.45x10-10 W sr-1 m-2 Hz-1 respectively. This gives a very low amount of useful radiation at Europa and an even smaller amount 67P/Churyumov–Gerasimenko, bringing extreme doubt on the use of this novel method.